Os fios e os rastros de O Vigilante Rodoviário: uma reflexão sobre o universo de criação e de produção de um seriado para a TV brasileira (1959-1962) - Picerni, Icaro (2015)
This work aims to study the television series O Vigilante Rodoviário in dialogical and synchronous way. In the first field, we studied their relations with the literary narrative, as the melodrama, through the affiliation to the classic Hollywood movies. In the second field, we analyzed the ways of Brazilian television, a period marked by many trials and fed by numerous serial American productions vying with national programs. Surviving after the bankruptcy of Film Company Maristela, Ary Fernandes and Alfredo Palacios created a television series that attracted the interests of the multinational Nestlé and that was broadcast on TV Tupi. This process does reflect on what being a pioneer within an even television in training and shows how the work sought to fit into hegemonic discourses to share some values with the urban middle class, who owned public capital to acquire an expensive receiver and inaccessible to the masses and do not constitute, therefore, a product of the culture industry. Internally, the representations of the series were studied in their cultural and pedagogical dimension. There is in it a Manicheans view of the world according to which the criminal evil never triumphs. On the other hand, the show presents the viewer values as legalism, respect for elders and hierarchies, the love of animals, the importance of collective security and the exaltation of the São Paulo State Highway Patrol. O Vigilante Rodoviário, on the one hand, conveys values of the urban upper middle class, and on the other, was established as an attempt to create a national industry pioneer series of programs. It can be seen as a quest to recover the national cinema, but limited by competition from American cinema hegemonic even in Brazil